提高法兰同轴度和圆跳动的应用研究 - 郭秀华; 陈祥林; 周曲珠 (Jixie chuandong)
Aiming at the problem of the accuracy of proper alignment and circle run-out of some reducer flange is not up to the requirement in the machining process,through technical analysis on the original processing of flange parts,the root reason of machining error is defined,and a special fixture is improved on the existing machining conditions,a new process scheme is proposed.It can guarantee the machining accuracy of proper alignment and circle run-out after trial-manufacture.